Growth kinetics of Kr nano structures encapsulated by graphene. (11th July 2018) - Yoo, S; Åhlgren, E H; Seo, J; Kim, W; Chiang, S; Kim, J-S
Abstract: Graphene can acquire salient properties by the intercalated nano structures, and to functionalize the graphene as designed, understanding the growth kinetics of the nano structures is a prerequisite. In that regards, Kr atoms are selectively intercalated just below the surface graphene of C(0001) by the incidence of low energy Kr ions. The growth kinetics of the encapsulated Kr nano structures is investigated by both scanning tunneling microscopy and molecular dynamics simulations. The intercalation proceeds via defect sites, such as surface vacancies. At room temperature, the thermal diffusion of intercalated Kr is almost frustrated by the strain field of the encapsulating graphene layers, and the growth of Kr nano structures proceeds via the transient mobility of both the intercalating Kr atoms and previously intercalated Kr atoms that are mobilized by collision with the incident Kr ions. At the elevated temperatures where thermal diffusion becomes effective, some Kr nano structures disappear, releasing pressurized Kr atoms, while others coalesce to form blisters via the delamination of the adjacent graphene. Some of the larger blisters explode to leave craters of varying depths at the surface. In contrast to growth on the substrate, the growth of each encapsulated nano structure depends significantly on extrinsic variables, such as surface vacancies and local topography around the nano structure, that affect the Kr diffusion and limit the maximal Kr pressure.